Granzyme B of cytotoxic T cells induces extramitochondrial reactive oxygen species production via caspase-dependent NADPH oxidase activation - Aguiló, Juan; Anel, Alberto; Catalán, Elena; Sebastián, Alvaro; Acín-Pérez, Rebeca; Naval, Javier; Wallich, Reinhard; Simon, Markus M.; Pardo, Julián (Immunology & cell biology, 2010)
Induction of reactive oxygen species (ROS) is a hallmark of granzyme B (gzmB)-mediated pro-apoptotic processes and target cell death. However, it is unclear to what extent the generated ROS derive from mitochondrial and/or extra-mitochondrial sources. To clarify this point, we have produced a mutant EL4 cell line, termed EL4-rho(0), which lacks mitochondrial DNA, associated with a decreased mitochondrial membrane potential and a defective ROS production through the electron transport chain of oxidative phosphorylation. When incubated with either recombinant gzmB plus streptolysin or ex vivo gzmB(+) cytotoxic T cells, EL4-rho(0) cells showed phosphatydylserine translocation, caspase 3 activation, Bak conformational change, cytochrome c release and apoptotic morphology comparable to EL4 cells. Moreover, EL4-rho(0) cells produced ROS at levels similar to EL4 under these conditions. GzmB-mediated ROS production was almost totally abolished in both cell lines by the pan-caspase inhibitor, Z-VAD-fmk. However, addition of apocynin, a specific inhibitor of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, led to a significant reduction of ROS production and cell death only in EL4-rho(0) but not EL4 cells. These data suggest that gzmB-induced cell death is accompanied by a caspase-dependent pathway of extra-mitochondrial ROS production, most probably through activation of NADPH oxidase.
Gesehen am 17.05.2021